Anna Freud : a view of development, disturbance and therapeutic techniques - Edgcumbe, Rose, 1934- (Makers of modern psychotherapy., 2000)
Rose Edgcumbe takes a fresh look at the relatively unknown contributions of Anna Freud's work to psychoanalytical theory and child development. The book highlights how her work is still relevant and important to the problems of society today.